Love Thy Neighbor? Central Asia in China’s New-Era Foreign Policy (2012–2024) - Pengfei Hou (Journal of Central Asian Studies, 2025)
Central Asia is critical to China’s security and development. Although China repeatedly underlines the necessity and urgency of establishing a good neighborhood with Central Asian countries, it has not released any strategies and specific policies, at least not explicitly. This article examines Central Asia’s sui generis in China’s new-era neighborhood diplomacy from 2012 to 2024. It contends that China’s foreign policies have evolved so subtly that Central Asia has been prioritized comparatively. With the aim of building a good neighborly relationship in mind, China has stepped up its engagement in Central Asia under the aegis of the Belt and Road Initiative, culminating in the China-Central Asia Summit in 2023.